Metachronous Multifocal Osteosarcoma Setelah 5 bulan terapi: Metastasis atau Lesi Primer Lain? - Astien, Astien; Hairunisa, Nany; Abikusno, Nugroho; Abikusno, Revalita; Agil, Nadifa; T, Febrina (Fakultas Kedokteran Universitas Trisakti, 2023)
Multifocal osteosarcoma is a rare form osteosarcoma. It is diagnosed by having two or more lesions without any visceral damage. Osteosarcoma is characterized by having concurrent numerous lesions; the synchronous type, and metachronous type are characterized by non-concurrent multiple lesions form. This case reports a boy 4 years old with a left femur osteosarcoma; histopathologically confirmed as chondroblastic osteosarcoma. After 5 months of chemotherapy, a new lesion was found at the left side of the cruris and pedis bones that were multiple, destructive, permeative, and exhibiting periosteal reaction. No visceral damage was found. In this case, the patient had a primary lesion and new non-concurrently lesions and no visceral damage, as conclusion was diagnosed as metachronous multifocal osteosarcoma that had never been reported in Indonesia.